Inflammatory cytokines, high-sensitivity C-reactive protein, and risk of one-year vascular events, death, and poor functional outcome after stroke and transient ischemic attack. Issue 2 (February 2022) - Coveney, S; Murphy, S; Belton, O; Cassidy, T; Crowe, M; Dolan, E; de Gaetano, M; Harbison, J; Horgan, G; Marnane, M; McCabe, JJ; Merwick, A; et al.
Background: Inflammation driven by pro-inflammatory cytokines is a new therapeutic target in coronary disease. Few data exist on the association of key upstream cytokines and post-stroke recurrence. In a prospective cohort study, we investigated the association between pivotal cytokines, high-sensitivity C-reactive protein (hsCRP) and one-year outcomes. Methods: BIO-STROKETIA is a multi-center prospective cohort study of non-severe ischemic stroke (modified Rankin score ≤ 3) and transient ischemic attack. Controls were patients with transient symptoms attending transient ischemic attack clinics with non-ischemic final diagnosis. Exclusion criteria were severe stroke, infection, and other pro-inflammatory disease; hsCRP and cytokines (interleukin (IL) 6, IL-1β, IL-8, IL-10, IL-12, interferon-γ (IFN-γ), tumor-necrosis factor-α (TNF-α)) were measured. The primary outcome was one-year recurrent stroke/coronary events (fatal and non-fatal). Results: In this study, 680 patients (439 stroke, 241 transient ischemic attack) and 68 controls were included. IL-6, IL-1β, IL-8, IFN-γ, TNF-α, and hsCRP were higher in stroke/transient ischemic attack cases (p ≤ 0.01 for all). On multivariable Cox regression, IL-6, IL-8, and hsCRP independently predicted one-year recurrent vascular events (adjusted hazard ratios (aHR) per-quartile increase IL-6 1.31, confidence interval (CI) 1.02–1.68, p = 0.03; IL-8 1.47, CI 1.15–1.89, p = 0.002; hsCRP 1.28, CI 1.01–1.62, p = 0.04). IL-6 (aHR 1.98, CI 1.26–3.14, p = 0.003) and hsCRP (aHR 1.81, CI 1.20–2.74, p = 0.005) independently predicted one-year fatality. IL-6 and hsCRP (adjusted odds ratio per-unit increase 1.02, CI 1.01–1.04) predicted poor functional outcome, with a trend for IL-1β (p = 0.054). Conclusion: Baseline inflammatory cytokines independently predicted late recurrence, supporting a rationale for randomized trials of anti-inflammatory agents for prevention after stroke and suggesting that targeted therapy to high-risk patients with high baseline inflammation may be beneficial.